EVALUATION OF OXIDATIVE STRESS IN DOGS WITH HEPATIC DYSFUNCTION - R.K.R. Sangamitra; G. Suganya; V. Leela; M. Balagangadhara Thilagar (Indian Journal of Veterinary and Animal Sciences Research, 2025)
The study was conducted to evaluate the oxidative stress in the dogs affected with parenchymal, biliary and neoplastic hepatic disorders compared with apparently healthy dogs. Twenty apparently healthy dogs framed the control group. The experimental group consist of twenty dogs in which 9 dogs formed the parenchymal disorder, six dogs with biliary disorder and five dogs with neoplastic disorder based on the serum biochemical and ultrasonographic investigation. The biochemical parameters such as Alanine aminotransferase (ALT), Alkaline phosphatase (ALP), total bilirubin and direct bilirubin were significantly elevated in experimental group whereas glucose concentration was decreased. In the present study Oxidative biomarkers such as Catalase (CAT), Superoxide dismutase (SOD) and Glutathione peroxidase (GPX) were significantly reduced and Thiobarbituric Acid Reacting Substance (TBARS) was significantly increased in parenchymal, biliary and neoplastic disorders of experimental group when compared with control group. Results of this study showed that the significant increase in oxidative stress in all three disorders of hepatic dysfunction in dogs could be the cause for the progress of hepatic pathology.